Prioritized averaging/geometric aggregation operators under the intuitionistic fuzzy soft set environment - Arora, R; Garg, H (Scientia Iranica. Transaction E, Industrial engineering, 2018)
Softset theory acts as a fundamental tool for handling uncertainty in the data by adding a parameterization factor during the process as compared to fuzzy and intuitionistic fuzzy set theory. In the present manuscript, the work has been done under environment of the Intuitionistic Fuzzy SoftSets (IFSSs), and some new averaging/ geometric prioritized aggregation operators have been proposed whose preferences, related to attributes, are made in the form of IFSSs. Their desirable properties have also been investigated. Furthermore, based on these operators, an approach to investigating the Multi-Criteria Decision Making (MCDM) problem has been presented. The effectiveness of these operators has been demonstrated through a case study.